Formulasi dan Uji Mutu Fisik Krim Antiperspirant dari Ekstrak Kunyit Putih (Curcuma zedoaria (Berg.) Roscoe) - Syafira, Nona; Dalimunthe , Gabena Indrayani; Lubis, Minda Sari; Nasution, Muhammad Amin (Journal of Pharmaceutical and Sciences, 2025)
Background: Curcuma zedoaria (Berg.) Roscoe, commonly known as white turmeric, is a plant from the Zingiberaceae family that contains bioactive compounds such as curcumin, flavonoids, alkaloids, saponins, and tannins. These compounds have potential as natural antiperspirants due to their astringent and antimicrobial properties, which can reduce sweat production and prevent body odor. The use of synthetic antiperspirants containing aluminum chloride often causes skin irritation, highlighting the need for safer, natural alternatives. Objective: This study aims to formulate an antiperspirant cream using white turmeric (Curcuma zedoaria (Berg.) Roscoe) extract with good physical quality and to evaluate the effectiveness of various concentrations in inhibiting sweat production. Methods: This experimental study involved extracting white turmeric using 96% ethanol through maceration, followed by concentration with a rotary evaporator. The antiperspirant cream was formulated with varying extract concentrations. Physical quality evaluations included organoleptic testing, homogeneity, pH, stability, viscosity, adhesion, spreadability, cream type, as well as irritation and antiperspirant tests on volunteers. Results: Phytochemical screening showed that the white turmeric extract contains alkaloids, flavonoids, saponins, and tannins. The cream with a 17.5% extract concentration demonstrated the highest antiperspirant effectiveness compared to 7.5% and 12.5% concentrations. All formulations met physical quality standards, including pH (4.5–6.5), viscosity (2,700–23,020 cP), and 14-day stability without significant changes. Conclusion: The white turmeric-based antiperspirant cream met physical quality standards and exhibited significant antiperspirant effects, particularly at a 17.5% concentration. This study demonstrates the potential of white turmeric as a safe and effective natural active ingredient in antiperspirant formulations.